(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The intellectual services market is one of the key drivers of modern economic growth, innovation, and competitiveness. Skilled professionals play a crucial role in shaping, expanding, and maintaining this market by providing high-value services that require specialized knowledge, creativity, and analytical capability. This article examines the significance of skilled professionals in the development of the intellectual services market, explores their contribution to innovation and knowledge transfer, and analyzes the main challenges related to human capital development in this sector. The findings indicate that continuous education, digital competence, and global collaboration are essential to strengthening intellectual service capacities and ensuring sustainable economic advancement.